Replication Data for: Semi-automatic Ice Rafted Debris quantification with Computed Tomography ... - Van Der Bilt, Willem Godert Maria (DataverseNO, 2021)
This dataset includes all analyses performed on the cores CT-scanned presented in Cederstrøm et al. 2021 – accepted in Paleoceanography and Paleoclimatology, but at the time of writing only accessible as a pre-print via https://www.essoar.org/doi/abs/10.1002/essoar.10506939.1. The data presented derive from two datasets. First, synthetic sediment archives (phantoms) that were spiked with approximately 25, 100, 500, 1000 and 2000 grains in the 150-500 µm fraction of different lithologies that are common in Ice Rafted Debris (IRD) source areas: basalt (B 0-4), dolomite (D 0-4), quartz (Q0-4), and a 1:1:1: mixture of each of the latter (M0-4). And secondly, sections of two natural sediment archives in which 150-500 µm sized IRD was counted at 2 cm intervals using standard manual protocols. Both of these cores, named GS16-204-22CC GS16-204-18CC, derive from East Greenland (Denmark Strait). The data are organized per paper figure per .txt file. The data behind Fig. 1 includes information on the composition ...